“Word of the Day”: Enhancing Student’s Vocabulary Through A Daily Strategy in EFL Classroom - Ashar, Aisyah; Marlianti, Rosyana; Wulandari, Nur; Fitri; Zakaria; Suryadi, Ray (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examined the use of the “Word of the Day” (WotD) strategy as a means of improving vocabulary mastery among ninth-grade students at SMP Negeri 2 Samaturu. The intervention lasted seven weeks and involved 119 students from four classes, using a classroom-based field research design. Daily vocabulary activities were integrated into lessons through interactive methods such as group work, quizzes, and simple games, while data were collected through observation, questionnaires, and interviews. The findings showed that the WotD strategy helped students consistently expand their vocabulary and apply new words in meaningful contexts. It also increased participation and motivation, as interactive activities encouraged learners to engage more actively in classroom communication. Some differences in student engagement were noted, with challenges including varying levels of motivation, discipline issues, and occasional school activity disruptions. Despite these constraints, the study highlights the potential of WotD as a low-cost and sustainable approach to vocabulary instruction in rural EFL classrooms, contributing both to lexical growth and to fostering learner engagement.